2023
DOI: 10.1113/jp283556
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal choline, folate and one‐carbon metabolism in mediating the impact of prenatal alcohol exposure on placental and fetal development

Abstract: Prenatal alcohol consumption (PAE) may be associated with a broad spectrum of impacts, ranging from no overt effects, to miscarriage, fetal growth restriction and fetal alcohol spectrum disorder. A major mechanism underlying the effects of PAE is considered to be altered DNA methylation and gene expression. Maternal nutritional status may be an important factor in determining the extent to which PAE impacts pregnancy outcomes, particularly the dietary micronutrients folate and choline because they provide meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Current treatment options for FASD involve supportive approaches such as motivational interviewing and the community-reinforcement approach. There is potential for proactive maternal nutritional intervention, including prenatal administration of antioxidant supplements, folic acid, choline, neuroactive peptides, and neurotrophic growth factors [20,128,129]. Recent suggestions indicate that targeting specific epigenetic mechanisms involved in regulating gene expression could hold significant clinical relevance for individuals with FASD [114].…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment options for FASD involve supportive approaches such as motivational interviewing and the community-reinforcement approach. There is potential for proactive maternal nutritional intervention, including prenatal administration of antioxidant supplements, folic acid, choline, neuroactive peptides, and neurotrophic growth factors [20,128,129]. Recent suggestions indicate that targeting specific epigenetic mechanisms involved in regulating gene expression could hold significant clinical relevance for individuals with FASD [114].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological (Krahe et al, 2009) (Naseer et al, 2011) and vitamin E (Wentzel et al, 2006), and choline-rich diets (Baker et al, 2023) have shown promising outcomes. Folate, a member of the vitamin B family, is crucial for cellular homeostasis, DNA synthesis, and amino acid metabolism (Steane et al, 2023). Folate heightens antioxidant defenses by increas-ing glutathione levels and reducing lipid oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…During gestation, maternal nutrition affects fetal growth and development via the mother-to-fetus interface. Folic acid and choline, essential nutrients during pregnancy, are involved in the synthesis of nucleotides and phospholipids, as well as methylation [2]. 5,10-methylenetetrahydrofolate dehydrogenase (MTHFD1) is the key enzyme in folic acid metabolism and participates in choline metabolism.…”
mentioning
confidence: 99%